The NHS Health Check in England: an evaluation of the first 4 years. Issue 1 (13th January 2016) - Robson, John; Dostal, Isabel; Sheikh, Aziz; Eldridge, Sandra; Madurasinghe, Vichithranie; Griffiths, Chris; Coupland, Carol; Hippisley-Cox, Julia
Abstract : Objectives: To describe implementation of a new national preventive programme to reduce cardiovascular morbidity. Design: Observational study over 4 years (April 2009—March 2013). Setting: 655 general practices across England from the QResearch database. Participants: Eligible adults aged 40–74 years including attendees at a National Health Service (NHS) Health Check. Intervention: NHS Health Check: routine structured cardiovascular check with support for behavioural change and in those at highest risk, treatment of risk factors and newly identified comorbidity. Results: Of 1.68 million people eligible for an NHS Health Check, 214 295 attended in the period 2009–12. Attendance quadrupled as the programme progressed; 5.8% in 2010 to 30.1% in 2012. Attendance was relatively higher among older people, of whom 19.6% of those eligible at age 60–74 years attended and 9.0% at age 40–59 years. Attendance by population groups at higher cardiovascular disease (CVD) risk, such as the more socially disadvantaged 14.9%, was higher than that of the more affluent 12.3%. Among attendees 7844 new cases of hypertension (38/1000 Checks), 1934 new cases of type 2 diabetes (9/1000 Checks) and 807 new cases of chronic kidney disease (4/1000 Checks) were identified. Of the 27 624 people found to be at high CVD risk (20% or more 10-year risk) when attending an NHS Health Check, 19.3% (5325) were newly prescribed statins and 8.8% (2438) were newly prescribed antihypertensive therapy. Conclusions: NHS Health Check coverage was lower than expected but showed year-on-year improvement. Newly identified comorbidities were an important feature of the NHS Health Checks. Statin treatment at national scale for 1 in 5 attendees at highest CVD risk is likely to have contributed to important reductions in their CVD events.